CONSEQUENCES OF LEGAL BREACH IN THE GOODS TRANSPORT AGREEMENT: AKIBAT HUKUM WANPRESTASI PADA PERJANJIAN PENGANGKUTAN BARANG - Melda Laia, Rini (LPPM UPMI, 2023)
Technological advances in the context of improving the standard of human life have brought major changes to the implementation of the contract for the carriage of goods between the sender and the carrier of goods. The purpose of this study was to find out and analyze the legal consequences of default on goods transport agreements. This type of research is normative with a statutory approach. The data used is secondary data consisting of primary and secondary legal materials. As a result of default in the agreement on the transportation of goods, the party who feels aggrieved can claim compensation for the loss he has suffered. Settlement can be done by way of litigation and non-litigation. For this reason, it is recommended that the parties bound by the agreement for the carriage of goods carry out the agreement in good faith so that there is no default.